Riggia puyensis n. sp. (Isopoda: Cymothoidae) parasitizing Chaetostoma breve and Chaetostoma microps (Siluriformes: Loricariidae) from Ecuador - Rodríguez Haro, Cecilia Elizabeth (2017)
A new isopod was found parasitizing Chaetostoma breve and Chaetostoma microps from the Puyo and Bobonaza rivers. The parasite found belongs to the Cymothoidae family and could be located within the genus Riggia instead of Artystone by the presence of abdominal plates fused with the telson. The specimens found represent a new species, Riggia puyensis n. sp., and could be distinguished from Riggia cryptocularis by the presence of developed eyes. The main difference of the new specie from Riggia nana and Riggia brasiliensis is the size, bigger compared with the first and smaller compared with the last species. Riggia acuticaudata have the maxilliped with simple setae, the palp without spination, and maxillule with five spines (two terminal and three subterminal) instead in R. puyensis n. sp. the maxilliped have plumose setae, the palp have spination (with one apical spine, two setae on middle article and one in the basal article) and the maxillule have five spines: two terminal, two subterminal and other spine lower to the others. Riggia paranaensis have similar size, same number of segments in the antena, and similar maxilla to R. puyensis n. sp., but the antennule in the new specie have seven segments instead 6 in R. paranaensis, the antennule and antenna present spines not mentioned in R. paranaensis. Besides, the relative position of the mandible in R. puyensis n. sp. is different compared with R. paranaensis, the maxillule have the same number of spines but with different disposition, and the maxilliped have simple setae in R. paranaensis but those are plumose in the new specie.